The Public Policy Implementation on The Pre-Marital Screening for Prospective Bride and Groom (A Study on The Implementation of The Regulation of The Regent of Pidie, Aceh, Number 54/ 2018) - Analiansyah, Analiansyah; Ulfatun, Cut (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2020)
The goal is consequential, but it has not been implemented appropriately. The purpose of this research is to explain the implementation of the health examination policy for the prospective brides and grooms in Pidie, Aceh. This research is a qualitative study, located in Mutiara Timur District, Pidie. The data were obtained through observation, interviews, and document study which were then analyzed by using Gindle’s theory of public policy. The results showed that the implementation of health examinations for the brides and grooms did not run well. The government has not prepared all the equipment needed for medical examinations which results in the inability of the screening procedures to detect certain diseases. Also, the community's low understanding of the noteworthiness of health examination persisted as the result of low socialization. They only considered it as sheer administrative requirements. In consequence, it caused a fiasco to achieve the goal of pre-marital screening, specifically to avoid every married couple contracted any disease, and as a preventive measure to decrease criminal behavior in the community. To get the desired outcomes, the Pidie Regency Government must provide all the instruments needed and carry out a joint movement to socialize this policy to the public.